Large-scale preparation method and application of sodium ion positive electrode material

Through the preparation method of sodium ion positive electrode material assisted by water reducer, the problems of long reaction time and small output of the preparation method of sodium ion battery positive electrode material in the prior art are solved, and efficient and safe preparation of sodium ion battery positive electrode material is achieved, which improves the preparation of sodium ion battery positive electrode material. The reversible capacity and electrochemical properties of the material support the industrial application of sodium ion batteries.

CN119230821APending Publication Date: 2024-12-31QINGDAO SAILIDA ENERGY STORAGE IND TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411430288.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The preparation method of the existing sodium ion battery positive electrode material NaxFex-1(PO4)x-2P2O7/C has bottlenecks such as long reaction time, small output, and difficult to meet industrial applications. The use of dispersants such as ethanol increases the manufacturing cost and poses safety risks. .

Method used

Using a large-scale safe preparation method assisted by water reducer, NaxFex-1 is prepared by mixing the sodium, iron, phosphorus and carbon sources in deionized water, grinding, spray drying and staged sintering treatment. PO4)x-2P2O7/C powder, optimize process parameters to reduce costs and improve safety.

Benefits of technology

The NaxFex-1(PO4)x-2P2O7/C was prepared in batch, safely and efficiently. The material has a reversible capacity of 110mAh·g-1 at a rate of 0.2C, and its particle size is adjustable and its morphology is uniform, which reduces the synthesis cost. , improves electrochemical performance and supports the industrial application of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230821A_ABST
    Figure CN119230821A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion batteries, and particularly relates to a large-scale safe preparation method of a sodium ion positive electrode material assisted by a water reducing agent. The preparation method comprises the following steps: putting a sodium source into a water reducing agent, then adding deionized water, finally adding an iron source, a phosphorus source and a carbon source into the mixed solution, and repeatedly grinding to obtain a homogeneous solution; drying the homogeneous solution to obtain a precursor; and carrying out staged sintering treatment on the precursor to finally obtain the NaxFex-1 (PO4) x-2P2O7 / C powder. The Na4Fe3 (PO4) 2P2O7 / C can be prepared in batches by limiting the types and process parameters of the sodium source, the iron source, the phosphorus source and the carbon source, and the reversible capacity of the obtained Na4Fe3 (PO4) 2P2O7 / C under the multiplying power of 0.2 C can reach up to 110 mAh. G <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion positive electrode material Na x Fe x-1 (PO4) x-2 A large-scale and safe preparation method for P2O7 / C. Background Art

[0002] With the rapid development of the global economy, energy crisis and environmental pollution problems are becoming more and more serious. The development and utilization of clean energy such as solar energy, wind energy, and ocean tidal energy has become an inevitable trend. Secondary batteries, as the most efficient energy storage technology, are a strong support for clean energy technology, and their research and development are of great significance. Lithium-ion batteries have high energy density and long cycle life. They are not only widely used in portable electronic devices, but also have developed rapidly in recent years as the preferred power source for electric vehicles and energy storage power stations. However, with the continuous expansion of global large-scale energy storage needs, the shortage of lithium resources on the earth will become a bottleneck restricting the large-scale application of lithium-ion batteries in the future. Sodium is in the same main group as lithium, and its chemical properties are similar to those of lithium. Its abundance in the earth's crust is 2.64%, which is much higher than lithium (0.006%). Therefore, the development of resource-rich and environmentally friendly sodium-ion battery technology is of great strategic significance and practical value to the development of large-scale energy storage technology. Iron-based polyanion sodium ion (Na2O3) with Pn21a structure x Fe x-1 (PO4) x-2 P2O7 / C, x=2,3 or 4) battery cathode materials have open sodium ion diffusion channels and good thermal and chemical stability. Among them, Na4Fe3(PO4)2P2O7 has a high theoretical specific capacity and excellent cycle performance, and is one of the most promising sodium ion battery cathode materials for industrialization. x Fe x-1 (PO4) x- The most commonly used methods for 2P2O7 / C materials are liquid phase method and mechanical solid phase method. x Fe x-1 (PO4) x-2P2O7 / C materials have long reaction times and low yields, which cannot meet the needs of industrialization; while the mechanical solid phase method mostly uses acetone and anhydrous ethanol as dispersants (Zheng JC, Yang BY, Wang XW, et al. Comparative Investigation of Na2FeP2O7 Sodium Insertion Material Synthesized by Using Different SodiumSources[J]. ACS Sustainable Chemistry&Engineering, 2018, 6(4): 4966-4972.)(Gao J, Tian Y, Mei Y, et al. Robust NASICON-type iron-based Na4Fe3(PO4)2(P2O7)cathode for high temperature sodium-ion batteries[J]. Chemical Engineering Journal, 2023, 458.), which poses huge safety risks in large-scale production and industrial applications. In addition, the uneconomical production using dispersants such as ethanol increases the manufacturing cost of sodium-ion batteries, making them unable to compete with lithium-ion batteries. Therefore, it is necessary to develop a low-cost and industrially scalable method for preparing Na x Fe x-1 (PO4) x-2 The P2O7 / C method is very important. Summary of the invention

[0003] In order to overcome the above-mentioned deficiencies in the prior art, the present invention aims to provide a sodium ion positive electrode material Na x Fe x-1 (PO4) x-2 Large-scale safe preparation method and application of P2O7 / C.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] A sodium ion cathode material Na assisted by a water reducing agent x Fe x-1 (PO4) x-2 A large-scale safe preparation method of P2O7 / C (2≤x≤4) comprises the following steps:

[0006] (1) placing a sodium source in a water reducing agent and stirring the mixture thoroughly, then adding deionized water, and finally adding an iron source, a phosphorus source, and a carbon source to the mixed solution and grinding the mixture repeatedly to obtain a homogeneous solution;

[0007] (2) drying the homogeneous solution obtained in step (1) to obtain a brown-grey precursor;

[0008] (3) The brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na x Fe x-1 (PO4) x-2 P2O7 / C powder, preferably x=2, 3 or 4.

[0009] The sodium source is one or more of sodium carbonate, sodium oxalate, sodium acetate, sodium pyrophosphate, sodium bicarbonate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate and disodium dihydrogen pyrophosphate.

[0010] The iron source is one or more of ferric nitrate, ferric acetate and ferrous oxalate

[0011] The phosphorus source is one or more of phosphoric acid, sodium phosphate, sodium pyrophosphate, ferric pyrophosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate and diammonium hydrogen phosphate.

[0012] The carbon source is one or more of glucose, sucrose, starch, glucose, oxalic acid, L-ascorbic acid, polyacrylonitrile, polyvinyl alcohol and citric acid.

[0013] The step (1) is performed by grinding with a sand mill, and the sand milling conditions are: a rotation speed of 500 rpm to 750 rpm and a time of 4 h to 6 h.

[0014] In the step (1), deionized water is used as a dispersant, the mass ratio of the water reducing agent to deionized water is 5:95 to 10:90, and the solid content of the homogeneous solution is 20% to 40%.

[0015] The ratio of the sodium source, iron source and phosphorus source in step (1) is as follows: x Fe x-1 (PO4) x-2 The stoichiometric ratio of the P2O7 / C material determines that the percentage of the carbon source in the total mass of the raw materials (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source) is 5-10%.

[0016] The water reducer is one or more of methacrylic acid-methyl acrylate polycarboxylic acid water reducer, acryl ether polycarboxylic acid water reducer, polyamide-polyimide polycarboxylic acid water reducer and amphoteric polycarboxylic acid water reducer.

[0017] The drying method in step (2) is spray drying, the air inlet temperature of the spray dryer is 990°C to 200°C, and the air outlet temperature is 40°C to 110°C.

[0018] The staged sintering process in step (3) adopts a two-stage heating process.

[0019] Furthermore, the two-stage temperature rise treatment is specifically as follows: the first stage is from room temperature to 300°C~350°C, and kept warm for 3h~6h; the second stage is from room temperature to 550°C~650°C, and kept warm for 6h~24h.

[0020] A positive electrode material Na prepared by the method x Fe x-1 (PO4) x-2 P2O7 / C.

[0021] Preferably, the method produces a sodium ion positive electrode material Na4Fe3(PO4)2P2O7 / C.

[0022] A kind of Na x Fe x-1 (PO4) x-2 Application of P2O7 / C in positive electrode materials for sodium ion batteries.

[0023] The beneficial effects of the present invention are:

[0024] 1. The present invention can prepare Na in batches by limiting the types of sodium source, iron source, phosphorus source, carbon source and process parameters. x Fe x-1 (PO4) x-2 P2O7 / C, obtained Na x Fe x-1 (PO4) x-2 The reversible capacity of P2O7 / C can reach up to 110 mAh g at a rate of 0.2C. -1 .

[0025] 2. The present invention can control the material with adjustable particle size and uniform morphology through spray drying technology.

[0026] 3. The present invention uses deionized water as a grinding aid, which greatly reduces the synthesis cost and improves safety.

[0027] 4. The present invention uses a water reducer to reduce the solubility of sodium salt in water, which can ensure the crystal form of the positive electrode material and thus greatly improve its electrochemical performance.

[0028] 5. The present invention adopts a staged sintering process, and extending the sintering time in the low temperature zone can fully eliminate the crystal water in the raw materials and reduce its influence on the material structure.

[0029] 6. The overall process of the present invention does not generate harmful gases, is green and environmentally friendly, and has low cost. It does not require the use of expensive transition metal doping and other complex methods, and is easy to prepare on an industrial scale.

[0030] 7. Na prepared by the present invention x Fe x-1 (PO4)x-2 As a positive electrode material for sodium ion batteries, P2O7 / C exhibits a high reversible capacity, providing support for the industrial preparation of polyanion positive electrode materials for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a SEM image of Na2FeP2O7 / C prepared in Example 1 of the present invention;

[0032] Figure 2 The XRD spectrum of Na2FeP2O7 / C prepared in Example 1 of the present invention;

[0033] Figure 3 This is a SEM image of Na3Fe2(PO4)P2O7 / C prepared in Example 3 of the present invention;

[0034] Figure 4 This is a SEM image of Na4Fe3(PO4)2P2O7 / C prepared in Example 6 of the present invention;

[0035] Figure 5 The XRD pattern of Na4Fe3(PO4)2P2O7 / C prepared in Example 6 of the present invention;

[0036] Figure 6 The charge and discharge curve of a button cell assembled using Na4Fe3(PO4)2P2O7 / C prepared in Example 6 of the present invention as a positive electrode material for a sodium ion battery;

[0037] Figure 7 This is the long cycle curve of the button cell assembled with Na4Fe3(PO4)2P2O7 / prepared in Example 6 of the present invention as the positive electrode material of the sodium ion battery.

[0038] Figure 8 This is the XRD spectrum of Na4Fe3(PO4)2P2O7 / C prepared in Comparative Example 1 of the present invention.

[0039] Fig. 9 The charge and discharge curves of button cells assembled using Na4Fe3(PO4)2P2O7 / C prepared in Comparative Example 1 of the present invention as the positive electrode material for sodium ion batteries.

[0040] Fig.10 This is the XRD spectrum of Na4Fe3(PO4)2P2O7 / C prepared in Comparative Example 2 of the present invention.

[0041] Fig.11 This is the charge and discharge curve of a button cell assembled using Na4Fe3(PO4)2P2O7 / C prepared in Comparative Example 2 of the present invention as the positive electrode material for a sodium ion battery. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0043] Example 1

[0044] The large-scale safe preparation method of the sodium ion positive electrode material Na2FeP2O7 / C assisted by a water reducing agent comprises the following steps:

[0045] Sodium bicarbonate is used as the sodium source, ferrous oxalate dihydrate is used as the iron source, ammonium dihydrogen phosphate is used as the phosphorus source, and L-ascorbic acid is used as the carbon source; the mass of the carbon source accounts for 5% of the total mass of the raw materials (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source).

[0046] (1) 3.79 kg of sodium bicarbonate was added to 2 kg of allyl ether polycarboxylate water reducer, and 20 kg of deionized water was added after stirring at room temperature for 0.5 h. 5.204 kg of ammonium dihydrogen phosphate, 4.038 kg of ferrous oxalate dihydrate and 0.6859 kg of L-ascorbic acid were added to the mixed solution. The mixed liquid was transferred to a sand mill for grinding at a speed of 500 rpm for 4 h to obtain a bright yellow homogeneous solution.

[0047] (2) placing the homogeneous solution obtained in step (1) in a spray dryer for drying at an air inlet temperature of 110° C. and an air outlet temperature of 80° C. to obtain a brown-gray precursor;

[0048] (3) Under the protection of inert gas, the brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na2FeP2O7 / C powder; wherein the staged sintering treatment is as follows: the temperature of the first stage is 300°C and kept warm for 6 hours, and the temperature of the second stage is increased to 650°C and kept warm for 6 hours.

[0049] The SEM image of Na2FeP2O7 / C prepared in Example 1 is shown in Figure 1 , the XRD pattern of Na2FeP2O7 / C is shown in Figure 2 ,Depend on Figure 1 It can be seen that the Na2FeP2O7 / C material has a shell-like morphology.

[0050] Example 2

[0051] A large-scale safe preparation method of a sodium ion positive electrode material Na3Fe2(PO4)P2O7 / C assisted by a water reducing agent comprises the following steps:

[0052] Sodium carbonate is used as the sodium source, ferrous oxalate dihydrate is used as the iron source, diammonium hydrogen phosphate is used as the phosphorus source, and starch is used as the carbon source; the mass of the carbon source accounts for 5% of the total mass of the raw materials (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source).

[0053] (1) 1.59 kg of sodium carbonate was added to 2 kg of polyamide-polyimide polycarboxylic acid water reducer, and 20 kg of deionized water was added after stirring at room temperature for 0.5 h. 3.634 kg of ferrous oxalate dihydrate, 4.02 kg of diammonium hydrogen phosphate and 0.4866 kg of starch were added to the mixed solution, and stirred at room temperature for 1 h. The mixed liquid was transferred to a sand mill for grinding at a speed of 650 rpm for 3 h to obtain a gray-green homogeneous solution.

[0054] (2) placing the gray-green homogeneous solution obtained in step (1) in a spray dryer for drying at an air inlet temperature of 110° C. and an air outlet temperature of 50° C. to obtain a brown-gray precursor;

[0055] (3) Under the protection of inert gas, the brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na3Fe2(PO4)P2O7 / C powder; wherein the staged sintering treatment is as follows: the first stage temperature is 300°C, and the temperature is kept for 6 hours; the second stage temperature is increased to 600°C and the temperature is kept for 12 hours.

[0056] Example 3

[0057] A large-scale safe preparation method of a sodium ion positive electrode material Na3Fe2(PO4)P2O7 / C assisted by a water reducing agent comprises the following steps:

[0058] Sodium acetate is used as the sodium source, ferrous oxalate dihydrate is used as the iron source, ammonium dihydrogen phosphate is used as the phosphorus source, and glucose is used as the carbon source; the mass of the carbon source accounts for 5% of the total mass of the raw materials (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source).

[0059] (1) 3.12 kg of sodium acetate was added to 1 kg of allyl ether polycarboxylate water reducer, and 19 kg of deionized water was added after stirring at room temperature for 0.5 h. 4.5425 kg of ferrous oxalate dihydrate, 4.378 kg of ammonium dihydrogen phosphate and 0.6338 kg of glucose were added to the mixed solution. The mixed liquid was transferred to a sand mill for grinding at a speed of 600 rpm for 2 h to obtain a homogeneous solution.

[0060] (2) placing the homogeneous solution obtained in step (1) in a spray dryer for drying at an air inlet temperature of 110° C. and an air outlet temperature of 70° C. to obtain a precursor;

[0061] (3) Under the protection of inert gas, the brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na3Fe2(PO4)P2O7 / C powder; wherein the staged sintering treatment is as follows: the first stage temperature is 300°C, and the temperature is kept for 6 hours; the second stage temperature is increased to 600°C and the temperature is kept for 18 hours.

[0062] The SEM image of Na3Fe2(PO4)P2O7 / C prepared in Example 3 is shown in Figure 3 ,Depend on Figure 3 It can be seen that the Na3Fe2(PO4)P2O7 / C material has a regular spherical morphology and regular size.

[0063] Example 4

[0064] A large-scale safe preparation method of a sodium ion positive electrode material Na3Fe2(PO4)P2O7 / C assisted by a water reducing agent comprises the following steps:

[0065] Sodium oxalate is used as the sodium source, ferric pyrophosphate is used as the iron source, ferric pyrophosphate is used as the phosphorus source, and glucose is used as the carbon source; the mass of the carbon source accounts for 5% of the total mass of the raw materials (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source).

[0066] (1) 3.367 kg of sodium oxalate was added to 2 kg of polyamide-polyimide polycarboxylic acid water reducer, and 20 kg of deionized water was added after stirring at room temperature for 0.5 h. 6.337 kg of ferric pyrophosphate and 0.5107 kg of glucose were added to the mixed solution. The mixed liquid was transferred to a sand mill for grinding at a speed of 500 rpm for 2 h to obtain a homogeneous solution;

[0067] (2) placing the homogeneous solution obtained in step (1) in a spray dryer for drying at an air inlet temperature of 120° C. and an air outlet temperature of 80° C. to obtain a precursor;

[0068] (3) Under the protection of inert gas, the brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na3Fe2(PO4)P2O7 / C powder; wherein the staged sintering treatment is as follows: the first stage temperature is 300°C, and the temperature is kept for 6 hours; the second stage temperature is increased to 600°C and the temperature is kept for 18 hours.

[0069] Example 5

[0070] A large-scale safe preparation method of a sodium ion positive electrode material Na3Fe2(PO4)P2O7 / C assisted by a water reducing agent comprises the following steps:

[0071] Sodium bicarbonate is used as the sodium source, ferric pyrophosphate is used as the iron source, ferric pyrophosphate is used as the phosphorus source, and glucose is used as the carbon source; the mass of the carbon source accounts for 5% of the total mass of the material (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source).

[0072] (1) 3.877 kg of sodium bicarbonate was added to 2.4 kg of polyamide-polyimide polycarboxylic acid water reducer, and 21.5 kg of deionized water was added after stirring at room temperature for 0.5 h. 5.85 kg of ferric pyrophosphate and 0.5119 kg of glucose were added to the mixed solution, and the mixed liquid was transferred to a sand mill for grinding at a speed of 550 rpm for 2 h to obtain a homogeneous solution;

[0073] (2) placing the homogeneous solution obtained in step (1) in a spray dryer for drying at an air inlet temperature of 130° C. and an air outlet temperature of 80° C. to obtain a precursor;

[0074] (3) Under the protection of inert gas, the brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na3Fe2(PO4)P2O7 / C powder; wherein the staged sintering treatment is as follows: the first stage temperature is 300°C, and the temperature is kept for 6 hours; the second stage temperature is increased to 600°C and the temperature is kept for 18 hours.

[0075] Example 6

[0076] A large-scale safe preparation method of a sodium ion positive electrode material Na4Fe3(PO4)2P2O7 / C assisted by a water reducing agent comprises the following steps:

[0077] Sodium oxalate is used as the sodium source, ferrous oxalate dihydrate is used as the iron source, diammonium hydrogen phosphate is used as the phosphorus source, and ascorbic acid is used as the carbon source; the mass of the carbon source accounts for 8% of the total mass of the raw materials (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source).

[0078] (1) 1.924 kg of sodium oxalate was added to 4 kg of polyamide-polyimide polycarboxylic acid water reducer, and 30 kg of deionized water was added after stirring at room temperature for 0.5 h. 3.89 kg of ferrous oxalate dihydrate, 3.715 kg of diammonium hydrogen phosphate and 0.8286 kg of ascorbic acid were added to the mixed solution. The mixed liquid was transferred to a sand mill for grinding at a speed of 550 rpm for 2 h to obtain a homogeneous solution.

[0079] (2) placing the homogeneous suspension obtained in step (1) in a spray dryer for drying at an air inlet temperature of 110° C. and an air outlet temperature of 80° C. to obtain a brown-gray precursor;

[0080] (3) Under the protection of inert gas, the brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na4Fe3(PO4)2P2O7 / C powder; wherein the staged sintering treatment is as follows: the first stage temperature is 300°C, and the temperature is kept for 6 hours; the second stage temperature is increased to 550°C, and the temperature is kept for 6 hours.

[0081] The SEM image of Na4Fe3(PO4)2P2O7 / C prepared in Example 6 is shown in Figure 4 , the XRD pattern of Na4Fe3(PO4)2P2O7 / C is shown in Figure 5 ,Depend on Figure 4 It can be seen that the Na4Fe3(PO4)2P2O7 / C material has a perfect spherical morphology, a wide size distribution, and a uniform surface carbon coating.

[0082] The Na4Fe3(PO4)2P2O7 / C powder obtained in Example 6 was used as the positive electrode material for sodium ion batteries to assemble button batteries in a glove box. Figure 6 The charge and discharge curves of button cells assembled with Na4Fe3(PO4)2P2O7 / C prepared in Example 6 as the positive electrode material of sodium ion batteries are shown in FIG. Figure 6 It can be seen that the reversible capacity can reach up to 110 mAh g at a rate of 0.2C. -1 . Figure 7 The long cycle curve of the button cell assembled with Na4Fe3(PO4)2P2O7 / C prepared in Example 6 as the positive electrode material of the sodium ion battery is shown in FIG. Figure 7 It can be seen that at a current density of 1C, the capacity retention rate is as high as 97% after 400 cycles.

[0083] Example 7

[0084] A large-scale safe preparation method of a sodium ion positive electrode material Na4Fe3(PO4)2P2O7 / C assisted by a water reducing agent comprises the following steps:

[0085] Sodium acetate is used as the sodium source, ferrous oxalate dihydrate is used as the iron source, ammonium dihydrogen phosphate is used as the phosphorus source, and ascorbic acid is used as the carbon source; the mass of the carbon source accounts for 5% of the total mass of the raw materials (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source).

[0086] (1) 3.044 kg of sodium acetate was added to 2 kg of allyl ether polycarboxylate water reducer, and 18 kg of deionized water was added after stirring at room temperature for 0.5 h. 4.9557 kg of ferrous oxalate dihydrate, 4.269 kg of ammonium dihydrogen phosphate and 0.6457 kg of ascorbic acid were added to the mixed solution; the mixed liquid was transferred to a sand mill for grinding at a speed of 600 rpm for 2 h to obtain a homogeneous solution;

[0087] (2) placing the homogeneous solution obtained in step (1) in a spray dryer for drying at an air inlet temperature of 130° C. and an air outlet temperature of 80° C. to obtain a brown-gray precursor;

[0088] (3) Under the protection of inert gas, the brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na4Fe3(PO4)2P2O7 / C powder; wherein the staged sintering treatment is as follows: the temperature of the first stage is 300°C, and the temperature is kept for 6 hours; the temperature of the second stage is increased to 600°C, and the temperature is kept for 6 hours.

[0089] Example 8

[0090] A large-scale safe preparation method of a sodium ion positive electrode material Na4Fe3(PO4)2P2O7 / C assisted by a water reducing agent comprises the following steps:

[0091] Sodium acetate is used as the sodium source, ferrous oxalate dihydrate is used as the iron source, ammonium dihydrogen phosphate is used as the phosphorus source, and ascorbic acid is used as the carbon source; the mass of the carbon source accounts for 5% of the total mass of the raw materials (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source).

[0092] (1) 3.044 kg of sodium acetate was added to 2 kg of methacrylic acid-methyl acrylate polycarboxylate water reducer, and 18 kg of deionized water was added after stirring at room temperature for 0.5 h. 4.9557 kg of ferrous oxalate dihydrate, 4.269 kg of ammonium dihydrogen phosphate and 0.6457 kg of ascorbic acid were added to the mixed solution; the mixed liquid was transferred to a sand mill for grinding at a speed of 600 rpm for 2 h to obtain a homogeneous solution;

[0093] (2) placing the homogeneous solution obtained in step (1) in a spray dryer for drying at an air inlet temperature of 130° C. and an air outlet temperature of 80° C. to obtain a brown-gray precursor;

[0094] (3) Under the protection of inert gas, the brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na4Fe3(PO4)2P2O7 / C powder; wherein the staged sintering treatment is as follows: the temperature of the first stage is 300°C, and the temperature is kept for 6 hours; the temperature of the second stage is increased to 600°C, and the temperature is kept for 6 hours.

[0095] Example 9

[0096] A large-scale safe preparation method of a sodium ion positive electrode material Na4Fe3(PO4)2P2O7 / C assisted by a water reducing agent comprises the following steps:

[0097] Sodium acetate is used as the sodium source, ferrous oxalate dihydrate is used as the iron source, ammonium dihydrogen phosphate is used as the phosphorus source, and ascorbic acid is used as the carbon source; the mass of the carbon source accounts for 5% of the total mass of the raw materials (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source).

[0098] (1) 3.044 kg of sodium acetate was added to 2 kg of amphoteric polycarboxylate water reducer, and 18 kg of deionized water was added after stirring at room temperature for 0.5 h. 4.9557 kg of ferrous oxalate dihydrate, 4.269 kg of ammonium dihydrogen phosphate and 0.6457 kg of ascorbic acid were added to the mixed solution; the mixed liquid was transferred to a sand mill for grinding at a speed of 600 rpm for 2 h to obtain a homogeneous solution;

[0099] (2) placing the homogeneous solution obtained in step (1) in a spray dryer for drying at an air inlet temperature of 130° C. and an air outlet temperature of 80° C. to obtain a brown-gray precursor;

[0100] (3) Under the protection of inert gas, the brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na4Fe3(PO4)2P2O7 / C powder; wherein the staged sintering treatment is as follows: the temperature of the first stage is 300°C, and the temperature is kept for 6 hours; the temperature of the second stage is increased to 600°C, and the temperature is kept for 6 hours.

[0101] Comparative Example 1

[0102] The difference from Example 6 is that no polyamide-polyimide polycarboxylic acid water reducer is added, and the rest is the same as Example 6, specifically:

[0103] Sodium oxalate is used as the sodium source, ferrous oxalate dihydrate is used as the iron source, diammonium hydrogen phosphate is used as the phosphorus source, and ascorbic acid is used as the carbon source; the mass of the carbon source accounts for 8% of the total mass of the raw materials (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source).

[0104] (1) 1.924 kg of sodium oxalate was added to 34 kg of deionized water, and the mixture was stirred at room temperature for 0.5 h. 3.89 kg of ferrous oxalate dihydrate, 3.715 kg of diammonium hydrogen phosphate and 0.8286 kg of ascorbic acid were added to the solution. The mixed liquid was transferred to a sand mill and ground at a speed of 550 rpm for 2 h to obtain a homogeneous solution.

[0105] (2) placing the homogeneous suspension obtained in step (1) in a spray dryer for drying at an air inlet temperature of 110° C. and an air outlet temperature of 80° C. to obtain a brown-gray precursor;

[0106] (3) Under the protection of inert gas, the brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na4Fe3(PO4)2P2O7 / C powder; wherein the staged sintering treatment is as follows: the first stage temperature is 300°C, and the temperature is kept for 6 hours; the second stage temperature is increased to 550°C, and the temperature is kept for 6 hours.

[0107] The XRD pattern of Na4Fe3(PO4)2P2O7 / C prepared in Comparative Example 1 is shown in Figure 8,Depend on Figure 8 It can be seen that without adding polyamide-polyimide polycarboxylic acid water reducer, obvious impurities appeared in the crystal form of Na4Fe3(PO4)2P2O7 / C material. Analysis showed that the appearance of impurities was caused by excessive loss of sodium oxalate during the drying process.

[0108] The Na4Fe3(PO4)2P2O7 / C powder obtained in Comparative Example 1 was used as a positive electrode material for sodium ion batteries to assemble button batteries in a glove box. Fig. 9 The charge and discharge curves of button cells assembled with Na4Fe3(PO4)2P2O7 / C prepared in Comparative Example 1 as the positive electrode material for sodium ion batteries are shown in Table 1. Fig. 9 It can be seen that the discharge capacity of the material at a rate of 0.2C is 99 mAh g -1 However, its first coulombic efficiency is greater than 100%, indicating that the material is in a sodium-deficient state, which limits its application prospects in full batteries. Therefore, the embodiment of the present invention uses a water reducer to reduce the solubility of sodium salt in water, which can ensure the crystal form of the positive electrode material and thereby greatly improve its electrochemical performance.

[0109] Comparative Example 2

[0110] The difference from Example 6 is that the segmented sintering is not used in the sintering process, and the rest is the same as Example 6, specifically:

[0111] Sodium oxalate is used as the sodium source, ferrous oxalate dihydrate is used as the iron source, diammonium hydrogen phosphate is used as the phosphorus source, and ascorbic acid is used as the carbon source; the mass of the carbon source accounts for 8% of the total mass of the raw materials (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source).

[0112] (1) 1.924 kg of sodium oxalate was added to 4 kg of polyamide-polyimide polycarboxylic acid water reducer, and 30 kg of deionized water was added after stirring at room temperature for 0.5 h. 3.89 kg of ferrous oxalate dihydrate, 3.715 kg of diammonium hydrogen phosphate and 0.8286 kg of ascorbic acid were added to the mixed solution. The mixed liquid was transferred to a sand mill for grinding at a speed of 550 rpm for 2 h to obtain a homogeneous solution.

[0113] (2) placing the homogeneous suspension obtained in step (1) in a spray dryer for drying at an air inlet temperature of 110° C. and an air outlet temperature of 80° C. to obtain a brown-gray precursor;

[0114] (3) Under the protection of an inert gas, the brown-gray precursor obtained in step (2) is sintered to finally obtain Na4Fe3(PO4)2P2O7 / C powder; wherein the sintering temperature is 550°C and the holding time is 12 h.

[0115] The XRD pattern of Na4Fe3(PO4)2P2O7 / C prepared in Comparative Example 2 is shown in Fig.10 ,Depend on Fig.10 It can be seen that without staged sintering, obvious impurity phases appeared in the crystal form of Na4Fe3(PO4)2P2O7 / C material. Analysis shows that the reaction time of Na4Fe3(PO4)2P2O7 / C material in the low temperature zone was insufficient, resulting in a certain proportion of impurity phases in the material.

[0116] The Na4Fe3(PO4)2P2O7 / C powder obtained in Comparative Example 2 was used as the positive electrode material for sodium ion batteries to assemble button batteries in a glove box. Fig.11 The charge and discharge curves of button cells assembled with Na4Fe3(PO4)2P2O7 / C prepared in Comparative Example 1 as the positive electrode material for sodium ion batteries are shown in Table 1. Fig.11 It can be seen that the discharge capacity of the material at a rate of 0.2C is only 100.3mAh·g -1 , which is significantly lower than 110 mAh·g in Example 6 -1 Therefore, the embodiment of the present invention adopts a staged sintering process, and prolonging the sintering time in the low temperature zone can fully eliminate the crystal water in the raw materials and reduce its influence on the material structure.

[0117] Comparative Example 3

[0118] The difference from Example 6 is that ascorbic acid is not added as a carbon source, and the percentage of carbon source to the total mass of the raw material is 0. The rest is the same as Example 6, specifically:

[0119] Sodium oxalate was used as the sodium source, ferrous oxalate dihydrate was used as the iron source, and diammonium hydrogen phosphate was used as the phosphorus source.

[0120] (1) 1.924 kg of sodium oxalate was added to 4 kg of polyamide-polyimide polycarboxylic acid water reducer, and 30 kg of deionized water was added after stirring at room temperature for 0.5 h. 3.89 kg of ferrous oxalate dihydrate and 3.715 kg of diammonium hydrogen phosphate were added to the mixed solution. The mixed liquid was transferred to a sand mill for grinding at a speed of 550 rpm for 2 h to obtain a homogeneous solution;

[0121] (2) placing the homogeneous suspension obtained in step (1) in a spray dryer for drying at an air inlet temperature of 110° C. and an air outlet temperature of 80° C. to obtain a brown-gray precursor;

[0122] (3) Under the protection of inert gas, the brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na4Fe3(PO4)2P2O7 powder; wherein the staged sintering treatment is as follows: the temperature of the first stage is 300°C, and the temperature is kept for 6 hours; the temperature of the second stage is increased to 550°C, and the temperature is kept for 6 hours.

[0123] Comparative Example 4

[0124] The difference from Example 6 is that the percentage of carbon source to the total mass of the raw materials is 15%, and the rest is the same as Example 6, specifically:

[0125] Sodium oxalate is used as the sodium source, ferrous oxalate dihydrate is used as the iron source, diammonium hydrogen phosphate is used as the phosphorus source, and ascorbic acid is used as the carbon source; the proportion of the carbon source to the total mass of the raw materials (the total mass of the sodium source, the iron source, the phosphorus source and the carbon source) is 15%.

[0126] (1) 1.924 kg of sodium oxalate was added to 4 kg of polyamide-polyimide polycarboxylic acid water reducer, and 30 kg of deionized water was added after stirring at room temperature for 0.5 h. 3.89 kg of ferrous oxalate dihydrate, 3.715 kg of diammonium hydrogen phosphate and 1.6816 kg of ascorbic acid were added to the mixed solution. The mixed liquid was transferred to a sand mill for grinding at a speed of 550 rpm for 2 h to obtain a homogeneous solution.

[0127] (2) placing the homogeneous suspension obtained in step (1) in a spray dryer for drying at an air inlet temperature of 110° C. and an air outlet temperature of 80° C. to obtain a brown-gray precursor;

[0128] (3) Under the protection of inert gas, the brown-gray precursor obtained in step (2) is sintered in stages to finally obtain Na4Fe3(PO4)2P2O7 / 0.15C powder; wherein, the staged sintering treatment is as follows: the first stage temperature is 300°C, and the temperature is kept for 6 hours; the second stage temperature is increased to 550°C and the temperature is kept for 6 hours.

[0129] The rate performance of Na4Fe3(PO4)2P2O7 / C powder crystal materials with different carbon source contents obtained by Example 6, Comparative Examples 3 and 4 is compared, see Table 1.

[0130] Table 1 Material rate performance (reversible capacity)

[0131] magnification Example 6 Comparative Example 3 Comparative Example 4 0.2C 110mAh / g 92mAh / g 103mAh / g 0.5C 109.4mAh / g 83mAh / g 92.6mAh / g 1C 108.3mAh / g 74mAh / g 88.3mAh / g 5C 103.2mAh / g 55.6mAh / g 80.8mAh / g 10C 88.3mAh / g 43.2mAh / g 71.9mAh / g 20C 82.5mAh / g 21mAh / g 60.4mAh / g

[0132] As can be seen from Table 1, the reversible capacities of Comparative Examples 3 and 4 under different rate conditions are significantly lower than those of Example 6. It can be seen that the present invention achieves a significant improvement in the rate performance of the material by adjusting the ratio of the mass of the carbon source to the total mass of the material. The reversible capacity can reach 110 mAh·g at a rate of 0.2C. -1 , so the obtained Na x Fe x-1 (PO4) x-2 As a positive electrode material for sodium ion batteries, P2O7 / C exhibits a high reversible capacity, providing support for the industrial preparation of polyanion positive electrode materials for sodium ion batteries.

[0133] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A sodium ion positive electrode material Na x Fe x-1 (PO4) x-2 The large-scale preparation method of P2O7 / C is characterized in that: The method comprises the following steps: (1) placing a sodium source in a water reducing agent, then adding deionized water, and finally adding an iron source, a phosphorus source, and a carbon source to the mixed solution and repeatedly grinding to obtain a homogeneous solution; (2) drying the homogeneous solution obtained in step (1) to obtain a precursor; (3) The precursor obtained in step (2) is sintered in stages to finally obtain Na x Fe x-1 (PO4) x-2 P2O7 / C (2≤x≤4) powder.

2. The sodium ion positive electrode material Na according to claim 1 x Fe x-1 (PO4) x-2 The large-scale preparation method of P2O7 / C is characterized in that: In step (1), the mass ratio of the water reducing agent to the deionized water is 5:95 to 10:90; the solid content of the homogeneous solution is 20% to 40%, and the ratio of the sodium source, the iron source and the phosphorus source is based on Na x Fe x-1 (PO4) x-2 The stoichiometric ratio of P2O7 / C material determines that the percentage of carbon source in the total mass of the raw material is 5-10%.

3. The sodium ion positive electrode material Na according to claim 1 x Fe x-1 (PO4) x-2 The large-scale preparation method of P2O7 / C is characterized in that: The grinding conditions in step (1) are: rotation speed 500 rpm to 750 rpm, and grinding time 4 to 6 hours.

4. The sodium ion positive electrode material Na according to claim 1 x Fe x-1 (PO4) x-2 The large-scale preparation method of P2O7 / C is characterized in that: The drying method of step (2) is spray drying, the air inlet temperature of the spray dryer is 90°C to 200°C, and the air outlet temperature is 40°C to 110°C.

5. The sodium ion positive electrode material Na according to claim 1 x Fe x-1 (PO4) x-2 The large-scale preparation method of P2O7 / C is characterized in that: The staged sintering treatment of step (3) is a two-stage heating treatment: the first stage is heating to 300°C-350°C and keeping warm for 3h-6h; the second stage is heating to 550°C-650°C and keeping warm for 6h-24h.

6. The sodium ion positive electrode material Na according to claim 1 x Fe x-1 (PO4) x-2 The large-scale preparation method of P2O7 / C is characterized in that: The sodium source is one or more of sodium carbonate, sodium oxalate, sodium acetate, sodium pyrophosphate, sodium bicarbonate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate or disodium dihydrogen pyrophosphate; The iron source is one or more of ferrous nitrate, ferrous acetate or ferrous oxalate dihydrate; The phosphorus source is one or more of phosphoric acid, sodium phosphate, sodium pyrophosphate, ferric pyrophosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate or diammonium hydrogen phosphate; The carbon source is one or more of glucose, sucrose, starch, glucose, oxalic acid, L-ascorbic acid, polyacrylonitrile, polyvinyl alcohol and citric acid.

7. The sodium ion positive electrode material Na according to claim 1 x Fe x-1 (PO4) x-2 The large-scale preparation method of P2O7 / C is characterized in that: The water reducer is one or more of methacrylic acid-methyl acrylate polycarboxylic acid water reducer, acryl ether polycarboxylic acid water reducer, polyamide-polyimide polycarboxylic acid water reducer or amphoteric polycarboxylic acid water reducer.

8. A sodium ion positive electrode material Na prepared by the method according to any one of claims 1 to 7 x Fe x-1 (PO4) x-2 P2O7 / C.

9. A Na according to claim 8 x Fe x-1 (PO4) x-2 Application of P2O7 / C in positive electrode materials for sodium ion batteries.